The euro and international capital markets - Carsten Detken; Philipp Hartmann (European Central Bank (ECB), 2000)
This paper provides a broad empirical examination of the major currencies' roles in international capital markets, with a special emphasis on the first year of the euro. A contribution is made as to how to measure these roles, both from the viewpoint of international financing as well as from the one of international investment activities. Time series of these new measures are presented, including euro aggregates calculated up to five years back in time. The data allow for the identification of changes in the role of the euro (or other main currencies) during 1999 compared to the aggregate of euro predecessor currencies, net of intra-euro area assets/ liabilities, before stage 3 of EMU. A number of key factors determining the currency distribution of international portfolio investments, such as relative market liquidity and relative risk characteristics of assets, are also examined empirically. It turns out that for almost all important market segments for which data are available, the euro immediately became the second most widely used currency for international financing and investment. For the flow of international bond and note issuance it has even slightly overtaken the US dollar in the second half of 1999. The data also suggest that this early supply of euro bonds by non-euro area residents, clearly exceeding the euro-predecessor currency aggregate, is actually absorbed by euro area residents and not y outside investors so far.
Keywords: G15; F32; G11; F21; 330; bank lending; bond markets; Capital flows; dollar; EMU; equity markets; euro; international capital markets; international currencies; international monetary system; money markets; portfolio selection; yen